Pengaruh Pengendalian Internal, SIA, dan Profesionalisme Auditor Internal, Terhadap Upaya Pencegahan Fraud Dalam Pengelolaan Persediaan - Ulfa Nita Dewi; Nadia Fathurrahmi Lawita; Dian Puji Puspitasari (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2021)
The purpose of this study is to examine the effect of Internal Inventory Control, Accounting Information Systems and Internal Auditor Professionalism on Fraud Prevention Efforts in Inventory Management. The population in this research are employees at CV Jaya Mitra Abadi. The sample of this research was 42 respondents. The sampling method in this study is non-probability sampling. The data used in this study are primary data, which is carried out using a survey method with a questionnaire. The processing method used is multiple linear regression. Based on the results of the study, it can be concluded that the variables of internal inventory control, accounting information systems and internal auditor professionalism have an effect on fraud prevention efforts in inventory management at CV Jaya Mitra Abadi.